Turkish Islamism in the Post-gezi Park Era (American Journal of Islam and Society, 2014)
The Gezi Park protests have stirred serious controversy both insideand outside Turkey on the JDP’s ruling style and ideology. By drawingon el-Affendi’s distinction between the Medina and Damascusmodels, I discuss the Islamist opposition to Erdoğan during the Gezievents. I argue that notwithstanding his recent Islamization policies,Erdoğan’s JDP is a conservative party that caters to Muslim nationalismwhile a new Islamism as an ethico-political ideal has been inthe making by the praxis of the new Islamist youth.